Pengaruh Kegiatan Tahfiz Al Quran terhadap Karakter Religius Anak Usia 8 sampai 12 Tahun di MDTA di Nagari Sungai Pua - Abdul Aziizirrahman; Jasmienti Jasmienti (Lembaga Yasin AlSys, 2026)
Qur’an memorization activities have received attention in various Islamic education studies because they are considered to play an important role in shaping children’s religious character. Nevertheless, research that specifically discusses the influence of Qur’an memorization activities on the religious character of children aged 8–12 years within the Madrasah Diniyah Takmiliyah Awaliyah (MDTA) setting, particularly in Nagari Sungai Pua, remains limited. This study aims to analyze the influence of Qur’an memorization activities on the religious character of children aged 8–12 years at MDTA in Nagari Sungai Pua. This study employed a quantitative approach with a correlational design and simple linear regression. The research participants consisted of 65 children selected using a saturated sampling technique. Data were collected through questionnaires, observation, and preliminary interviews and were then analyzed using descriptive statistics, Pearson correlation, and simple linear regression with the assistance of SPSS. The results showed that Qur’an memorization activities had a positive and significant influence on children’s religious character, with a significance value of 0.000 (< 0.05) and a correlation coefficient of 0.721. In addition, Qur’an memorization activities contributed 52% to the formation of children’s religious character. These findings strengthen religious education theory and the concept of religiosity based on the internalization of Qur’anic values in daily life. The conclusion of this study affirms the importance of Qur’an memorization activities in shaping children’s religious character through the habituation of worship, discipline, and responsibility. The implications of this study include theoretical contributions to the development of Qur’an-based character education and practical implications for Islamic educational institutions in improving the quality of Qur’an memorization programs.